2020
DOI: 10.1534/g3.119.400882
|View full text |Cite|
|
Sign up to set email alerts
|

Transcription Profiles of Age-at-Maturity-Associated Genes Suggest Cell Fate Commitment Regulation as a Key Factor in the Atlantic Salmon Maturation Process

Abstract: Despite recent taxonomic diversification in studies linking genotype with phenotype, follow-up studies aimed at understanding the molecular processes of such genotype-phenotype associations remain rare. The age at which an individual reaches sexual maturity is an important fitness trait in many wild species. However, the molecular mechanisms regulating maturation timing processes remain obscure. A recent genome-wide association study in Atlantic salmon (Salmo salar) identified large-effect age-at-maturity-asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 94 publications
(145 reference statements)
3
66
0
Order By: Relevance
“…Vgll3 expression in the heart was high relative to other tissues (Fig 2A), but also very variable, similar to results from three-year old juveniles from natural populations [28]. Expression in liver showed a linear downward trend from younger to older individuals, although the overall expression level remained very low relative to other tissues (S4 Fig).…”
Section: Vgll3 Expression Correlates With Maturation Inhibitionsupporting
confidence: 77%
See 4 more Smart Citations
“…Vgll3 expression in the heart was high relative to other tissues (Fig 2A), but also very variable, similar to results from three-year old juveniles from natural populations [28]. Expression in liver showed a linear downward trend from younger to older individuals, although the overall expression level remained very low relative to other tissues (S4 Fig).…”
Section: Vgll3 Expression Correlates With Maturation Inhibitionsupporting
confidence: 77%
“…Consistent with this, by analyzing RNAsequencing data from immature, prepubertal and pubertal testes, we found that vgll3 and yap1 showed opposite expression patterns with respect to maturity status. Salmon vgll3 expression was also found to negatively correlate with yap1 expression in early development [28]. We hypothesize that changes in vgll3 isoform abundance associated with vgll3 � E and vgll3 � L alleles may influence the tendency of cell differentiation in immature testes by changing interaction between Vgll3 and TEADs and/or Vgll3-Yap (Fig 6).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations